Manajemen Pengembangan Kewirausahaan (Entrepreneurship) Siswa SMKN-2 Palangkaraya - Iin Nurbudiyani (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The purpose of this research is to describe the management of developing entrepreneurship of SMKN-2 Palangkaraya students, including the function of planning, organizing, actuating, and evaluating. This research employs the qualitative phenomenology method, which is profoundly and naturally to understand and interpret the phenomena in the field. The subjects of the study were the headmaster, vice-headmaster in curriculum affairs, entrepreneurship teacher, and unit production manager. The data was collected through in-depth interviews, observation, and documentation. This research used Mile and Huberman analysis models through data reduction, data display, and conclusion. 1) The syllabus is not completely matched with the characteristics of Vocational High School 2, in which teaching and learning are focused on the cognitive aspects of students without giving practice in managing entrepreneurial activities, 2 ) Entrepreneurship class program has not reached the goal, because of not having a formal legality actuating the entrepreneurship program, and is an understanding of its curricula, so that the entrepreneurship class is program canceled for evaluation, event through the student's skill is reasonably good , 3) The training at the production unit could increase the student's ability and entrepreneurship, and 4) Industrial practices that have direct experiences to work and learn to manage the business in real time life situation.